2011
DOI: 10.5558/tfc87023-1
|View full text |Cite
|
Sign up to set email alerts
|

An ecological land classification approach to modeling the production of forest biomass

Abstract: Forest site classification is a prerequisite to successful integrated forest resources planning and management. Traditionally, site classification has emphasized a phytocentric approach, with tools such as the site index having a rich and long history in forest site evaluation. The concept of site index was primarily devised to assess site productivity of an even-aged, single-species stand. Site index has been the primary method of forest site evaluation in support of management for traditional forest products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…Our study revealed issues that contradict expert knowledge based concepts respected for decades with respect to approaches via formal quantification of available data, which is consistent with a recent call for advanced classifications in Europe [46,92,93], and in North America [86,87,[94][95][96]. Findings of this study may point to similar problems accompanying other classifications where landscape units may not be as strong as expected.…”
Section: Perspectives Of Ecological Classificationssupporting
confidence: 82%
“…Our study revealed issues that contradict expert knowledge based concepts respected for decades with respect to approaches via formal quantification of available data, which is consistent with a recent call for advanced classifications in Europe [46,92,93], and in North America [86,87,[94][95][96]. Findings of this study may point to similar problems accompanying other classifications where landscape units may not be as strong as expected.…”
Section: Perspectives Of Ecological Classificationssupporting
confidence: 82%
“…It is thus not particularly surprising that there would be differences in productivity. We quantified these differences using site index, which is widely employed to assess overall stand productivity or quality (Pokharel and Dech 2011), but which has some recognized limitations. Site index is an indirect measurement due to the fact that the top height at age 50 can only be directly meas- For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and Huang (2000) observed height and growth patterns of white spruce for the five major natural subregions in Alberta, and found that height was significantly different for one of the subregions, resulting in volume estimation errors up to 25% when the provincial height and site index curve was applied to this subregion. We are aware of no prior studies that examine ecosite classification with growth and yield model outputs from MIST; however, Pokharel and Dech (2011) have argued more broadly that a phytogeocentric approach to ecological land classification is essential to stratifying landscapes into ecologically meaningful units for management decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between ecosite, growth rate and wood anatomy may be quantified by a model that links microscopic properties (e.g., wood fibre length) to the landscape scale (e.g., site quality indicators) [16]. The use of ecosites as a base unit for modeling can be viewed as a more holistic (sensu Billings [17]) approach to creating growth and yield models in forestry, as ecosite classification captures many aspects of the complex environment [18]. Nonparametric hierarchical classification models such as regression tree analyses and random forests [19] provide a good approach for developing models that make predictions about wood fibre attributes for specific ecosites at the landscape scale.…”
Section: Introductionmentioning
confidence: 99%